Angular scattering measurements and modelling from building surfaces at sub‐THz frequencies between 92‐110 GHz - Demos Serghiou; Mohsen Khalily; Tim Brown; Rahim Tafazolli (Electronics Letters)
Abstract This letter presents experimental angularly resolved measurements and a model framework for characterizing continuous wideband reflection coefficients at sub‐terahertz frequencies between 92 and 110 GHz. Surfaces that appear “smooth” but with internal features comparable to the wavelength have shown to cause frequency selective scattering. An nth‐degree polynomial regression model is employed to quantify non‐linear multi‐path scattering that cannot be described by a best‐fit line, with least‐squares regression applied to find the best‐fitting polynomial and hence the coefficients. The obtained coefficients are then validated against the delay domain statistics of the propagation channel, demonstrating the proposed model's good agreement with measurements and its efficiency in reproducing angle‐dependent reflection coefficients for use in ray‐tracing tools.